Sodium ferulate alleviated paracetamol-induced liver toxicity in mice - Wang Hui; Peng Ren-xiu (Acta Pharmacologica Sinica, 2016)
Sodium ferulate (SF) is one of the effective components of Angelica sinensis Diels. Pretreatment with SF (100 mg.kg-1 ig, qd x 10 d) inhibited the activity of serum alanine aminotransferase, prevented the depletion of liver glycogen and glutathione, increased the liver homogenate and microsomal glutathione S-transferase activities, and reduced the malondialdehyde content, the membrane fluidity of liver microsome and the mitochondria in paracetamol (130 mg.kg-1, ip)-induced liver toxicity in mice. These results demonstrated the hepato-protective action of SF in mice